2018
DOI: 10.1007/s10240-018-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Fourier interpolation on the real line

Abstract: We use weakly holomorphic modular forms for the Hecke theta group to construct an explicit interpolation formula for Schwartz functions on the real line. The formula expresses the value of a function at any given point in terms of the values of the function and its Fourier transform on the set {0, ± √

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…Finally let us remark that our result admits a natural generalization to the space of even/odd functions with 4W T replaced by 2W T . This result also perfectly matches interpolation formulas from [2] and [7].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally let us remark that our result admits a natural generalization to the space of even/odd functions with 4W T replaced by 2W T . This result also perfectly matches interpolation formulas from [2] and [7].…”
Section: Introductionsupporting
confidence: 87%
“…In the recent breakthrough paper [7] Radchenko and Viazovska showed that any Schwartz function can be effectively reconstructed from the values of it and its Fourier transform at the points ± √ n, n ∈ Z ≥0 and two more values f (0),f (0). If we consider the counting function n (R) = | ∩ [−R, R]|, which in the case = {± √ n} takes the form n (R) = 1 + 2[R 2 ], we see that it satisfies the inequality n (W ) + n (T ) ≥ 4W T − O(1) for all W , T .…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the equality conditions for h in Theorem 2.1 are identical, except that the conditions f (r 1 ) = 0 and f (0) = 0 are replaced with h(r 1 ) = 0. These conditions arise naturally in interpolation problems [44,82]. Specifically, Open Problem 7.3 from [44] raised the question of whether radial Schwartz functions g : R d → R are uniquely determined by the values and radial derivatives of g and g at the radii r n for n ≥ 1.…”
Section: Bounds For the Average Kissing Numbermentioning
confidence: 99%
“…The function Φ may be thought of as a Gauss-Schrödinger transform of φ, given that the integral kernel Ĝτ is the fundamental solution of a Schrödinger equation without potential. We now rewrite the relationships [3] and [4] using integration by parts. If φ is a tempered test function, integration by parts applied to [3] gives that…”
mentioning
confidence: 99%